The Technology of Deception in Sergei Dovlatov’s Stories (Based on example of Certain Verbs) - GAZAROVA, DIANA (Bulletin of Yerevan University H: Russian Philology, 2021)
The paper is devoted to the ways of expression of the concept “deception” in S. Dovlatov’s works, to the comparison of the verbs “обманывать”, “лгать”, “врать” and “молчать” and their meanings in Russian linguoculture and the features of their using in Dovlatov’s stories, where lie is manifested in two forms: active and passive.